Pengaruh Penggunaan Celebrity Endorserdalammenarik Minat Beli Pengguna Media Sosial Instagram(Studi Kasus Mahasiswa FIS UINSU) - Ghasani, Thahira; Monang, Sori; Rozi, Fakhrur (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This research is entitled The Effect of Using Celebrity Endorsers in Attracting Interest in Buying Instagram Social Media Users (Case Study of FISUINSU Students). The purpose of this study was to determine the effect of x1 attractiveness (attractiveness), x2 trustworthiness (trust), and x3 expertise (expertise) owned by celebrity endorsers on buying interest of Instagram social media users. Data was collected through the questionnaire method with a population of 615 using the slovin formula, so 86 samples were obtained. Then an analysis of the data obtained was carried out in the form of quantitative analysis which included validity, reliability tests, through the f test and t test to prove the hypothesis. The data used is multiple linear regression analysis which functions to see the effect. Based on the results of the analysis of hypothesis testing (t test) which is processed using SPSS 22 Attractiveness variables (attractiveness) affect purchase intention with a value of Sig. 0.001 <0.05, Trustworthiness has no effect on buying interest with a Sig value. 0.215> 0.05, Expertise (expertise) affects the purchase intention with a value of Sig. 0.000 < 0.05, from the results of the t test it is found that one of the variables, namely trustworthiness, has no significant effect on the purchase intention of Instagram social media users. In the test of the coefficient of determination, together the variables Attractiveness (attractiveness), Trustworthiness (trust), Expertise (skills) affect the purchase intention of 82.4%. The remaining 17.6% Purchase intention (Y) is influenced by other variables not used in this study.